Planning Strategies for Inclusion in Education: challenges for discussion - Mylene Cristina Santiago; Mônica Pereira dos Santos (Universidade Federal do Rio Grande do Sul, 2015)
The present paper aims to analyze the continued education process of teachers who work at the Special Education Sector of Rio de Janeiro state, Brazil. On the basis of what we have named an omnilectical perspective of analysis, we analyze the planning of educational activities that aim to dislocate our standpoints from the disability to the students' potentials. Methodologically, we conducted group interviews during 2012 and a 60-hour Continued Education Cycle in 2013. The results point to the importance of pedagogic planning as an investigation/action process that calls for the participation of school subjects in both reflecting about and transforming school reality.